A Study on the Teaching of Mathematics in English at an 8th Grade Class at Doan Thi Diem Private Secondary School . M.A. Thesis Linguistics: 60 14 01 - Trần, Thị Thùy (University of Languages and International Studies, 2017)
Math, Science and Literature have been taught to ELLs in parts of the word. This research studies on the subject of Math because it is universal to people more than any others; its aims are to examine whether teaching Math in English is beneficial or not , t he teaching methods used by the Math teacher, the challenges of teaching Math in English in 8M at DTD School and to find out the recommendations to improve the situation of teaching Math in English in the future. To fulfill these targets, three instruments employed to collect data were the classroom observations, the questionnaire for the students and the interview for the Math teacher. The study was carried out and involved an American teacher of Math and 16 Vietnamese students in grade 8 at DTD School. S tatistical analysis revealed that most of the students initially struggled with mathematical vocabulary, cultural differences in teachers’ teaching methods and students’ learning styles and especially, their English limited proficiency. Gradually, they had improvement in their English competence and mathematical knowledge thanks to the Math teacher’s relatively well - planned lessons. Several strategies which are recommended to deal with the found challenges include differentiating specific instructions, teac hing mathematical vocabulary properly, applying technology, enhancing communications among students, parents, teacher and school and holding more Math competitions to encourage students to study Math in English.